The management of childhood drowning in a tertiary hospital in Indonesia: a case report - Dyah Kanya Wati; I Gde Doddy Kurnia Indrawan; Nyoman Gina Henny Kristianti; Felicia Anita Wijaya; Desak Made Widiastiti Arga; Arya Krisna Manggala (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
The World Health Organization (WHO) stated that drowning becomes the third leading cause of death from unintentional injury. Furthermore it was reported more than 372,000 cases of death annually among children due to drowning accident. Inappropriate of resuscitation attempt, delay in early management, inappropriate monitoring and evaluation lead to drowning complications riks even death. However, studies concerning the management of childhood drowning in Indonesia is limited. Here, we reported a case of childhood drowning in Sanglah General Hospital in Denpasar, Bali. An 8 years old girl arrived at the hospital with deterioration of consciousness after found drowning in the swimming pool. The management of the case was performed according to the recent literature guidelines. The first attempt was performed by resuscitation, followed by pharmacological interventions using corticosteroids, non-invasive ventilation and series of laboratory examination. With regular follow up, patient showed good recovery and prognosis.